Enhancing the protection of Human Rights of Persons with Disabilities: how is Malaysia progressing - Fauzi, Husna (Corner Resources Sdn. Bhd., Bandar Baru Bangi, Selangor, 2016)
Persons with disabilities remain as one of the vulnerable groups who often been discriminated against and marginalised from the mainstream development programmes in almost all societies. Being a disadvantaged group, they suffer from social exclusion, denied the basic rights and freedoms enjoyed by everyone else and being deprived of the opportunities to reach their potential. They have a long experience of being perceived as the recipients of welfare and charity rather than rights holders. In Malaysia, persons with disabilities have been identified as one of the target groups in the National Welfare Policy 1990. The policy aims to uplift the potential and to provide equal opportunities to the disabled persons, so that they would not be left out in the development of the country. Within the span of over thirty years after the endorsement of this policy, the governmental and non-governmental organisations continue to provide various programmes and services to cater for the special needs and interests of the disabled persons. In respect of legal protection provided to the disabled, the enforcement of the Persons with Disabilities Act 2008 seemed by many as particularly timely. This paper begins with a brief introduction on the statistics of persons with disabilities in Malaysia. This is followed by a general discussion on the paradigm shift of the model of disability. Thereafter, the paper highlights the existing policies, programmes and services available to the persons with disabilities in Malaysia. The paper then examines the relevant legislations that afford protection to the persons with disabilities in Malaysia, in particular focussing on the significant of the Persons with Disabilities Act 2008. The article concludes with some suggestions towards improving the overall well-being of the disabled persons.